Impacts of a conversation wheel between pregnant women and medicine students (Research, Society and Development, 2023)
Faced with a reality in which reliable popular knowledge and untruths routinely mix, it is necessary to investigate the impacts of dialogue on the formation of a critical conscience. In this sense, the experience report had the following objective: to report the experience of pregnant women and medical students in a conversation circle as a space for the collective construction of knowledge. Starting from an observational, descriptive study with a qualitative approach, it was observed, during the experience of the conversation wheel, the persistence of beliefs involving normal childbirth, given that, when listing truths and myths about humanized childbirth, many of the myths were part of the context of the pregnant women, including information still propagated by health professionals. It also became evident that the users were unaware of their rights during childbirth and how the absence of this information favors the occurrence of episodes of obstetric violence in a unique moment of significant vulnerability, childbirth. In addition, medical students involved in the event benefited from experiencing practices that go beyond theory, such as improving communication skills, autonomy in studies and transforming reality through knowledge. From the idealized dynamics based on PBL teaching, it is concluded that information sharing is the master way in demystifying inadequate knowledge and in building women aware of their rights, since female empowerment and knowledge are closely intertwined